Kepedulian Orang Tua terhadap Pendidikan Agama Islam pada Anak Tingkat Sekolah Dasar - Auliani, Nanda (Ahdāf: Jurnal Pendidikan Agama Islam, 2023)
This study analyzes the formulation of parental concern for Islamic religious education in elementary school children in Gampong Payabili Lhokseumawe. The purpose of this study was to explain how parents care about Islamic religious education for elementary school children in Gampong Payabili and describe the obstacles faced by parents in providing Islamic religious education to elementary school children in Gampong Payabili. The type of research used is qualitative with a descriptive approach. The data sources in this study were parents and elementary school level children in Gampong Payabili. Data collection techniques in the form of interviews, observation, and documentation. Data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. The results showed that parents' concern for Islamic religious education in elementary school level children in Gampong Payabili Lhokseumawe was shown by the supervision and direction given to children. As for the obstacles found, among others, parents have not fully provided facilities for children's learning needs, the lack of time that parents have in accompanying children due to being busy working and the minimal level of education of parents. To make up for their shortcomings, parents in Gampong Payabili try to be good role models for their children.